LEGAL PROTECTION OF EMPLOYMENT CONTRACT AGREEMENTS BETWEEN CLUB AND FOOTBALL PLAYERS IN CASES OF BREACH OF WAGE PAYMENT - Safara, Rianda; Ramadhani, Nova Arfiana; Fayura, Adelia Putri; Sari, Alya (Universitas Negeri Surabaya, 2024)
Football is one of the most popular sports in the world. With its rapid development, a national football organization called PSSI or the All Indonesia Football Association was formed. There are quite a few problems faced by Indonesian football players related to work contract issues, one of which is the problem of late payment of football players' wages by football clubs. Football athletes themselves are still referred to as workers or laborers and are subject to the Manpower Law so that the problems faced by athletes must be based on the Manpower Law. The purpose of this study is to determine the form of legal protection for football players when problems arise between football players and clubs related to wages that are not paid on time.